THE ESSENCE AND MODERN CONTENT OF THE «POLITICAL UNITY» CONCEPT - A. A. Albogachiev; M. M. Khamatkhanova; R. B. Gandaloev (Современная наука и инновации, 2022)
The article actualizes the concept of political unity within the framework of a dialectical understanding of the essence of unity as a process of internal integration of the foundations of political and national security. Within the framework of traditional scientific approaches, the very concept of "unity" can represent a multi-valued functional category of research, which conditionally politicizes almost all the processes taking place in Russia. The types of political and social interaction are identified as the basis for forming the content of political unity in the context of developing national security strategies in Russia. The author presents an overview of the conceptual features of the transformation of categories of political unity within the framework of ongoing socio-economic processes of society that politicize all spheres of life in modern Russia. The conclusion of the article is the substantiation of the content of political unity as a factor of national security, which allows regulating internal political processes in a rather unstable period of accelerating political reforms.